Maggot debridement therapy for the treatment of diabetic foot ulcers: robbing the rich past to give to the sore - Cutteridge, Joseph; Bera, Katarzyna (Journal of the Nuffield Department of Surgical Sciences, 2021)
A diabetic foot ulcer (DFU) is a serious complication of diabetes mellitus that results in significant morbidity and mortality. The lifetime risk of a patient with diabetes developing a DFU is 15-25%1. Furthermore, the incidence of DFUs is increasing in line with the growing burden of diabetes worldwide. The number of lower limb amputations secondary to diabetes has reached an all-time high in England, with 26,378 recorded from 2014-2017, an increase of 19.4% from 2010-20132. Maggot debridement therapy (MDT) involves the application of sterile larvae, usually of the species Lucilla sericata (common green bottle fly), which remove devitalised tissue to promote wound healing. This historical therapy re-emerged in the 1990s to combat the increasing incidence of recalcitrant wounds, such as DFUs. Since its reintroduction, there has been ongoing debate in the medical literature regarding the efficacy of MDT in the treatment of DFUs and other chronic wounds. We present the case of a 57-year-old male admitted with diabetic foot sepsis and multiorgan failure and discuss how MDT was used to complement initial surgical and antibiotic management. A 14-day course of MDT improved wound debridement and decreased necrotic tissue burden, after which no further surgical interventions were needed. This case provides further evidence that MDT is effective in the selective debridement of necrotic tissue and can aid the preservation of limb length in DFU patients, thereby highlighting the importance of MDT in multispecialist diabetic foot care.